Fractal geometry as an effective heat sink - Ramšak, Matjaž (Strojniški vestnik, 2022)
"How long is the coast of Britain?" was the question stated by Mandelbrot. Using smaller and smaller rulers the coast length limits to infinity. If this logic is applied to the fractal heat sink geometry, infinite cooling capacity should be obtained using fractals with mathematically infinite surface area. The aim of this article is to check this idea using Richardson extrapolation of numerical simulation results varying the fractal element length from one to zero. As expected, the extrapolated heat flux has a noninfinite limit. The presented fractal heat sink geometry is non-competitive to the straight fins.
Keywords: boundary element method; conjugate heat transfer; CPU cooling; CPU hlajenje; fractal heat sink; fraktalno hladilno telo; Koch snowflake; Kochova snežinka; konjugirani prenos toplote; laminar flow; laminarni tok; LED cooling; LED hlajenje; metoda robnih elementov